1998
DOI: 10.1042/bj3300479
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of sheep liver sorbitol dehydrogenase

Abstract: The substrate specificity of sheep liver sorbitol dehydrogenase has been studied by steady-state kinetics over the range pH 7-10. Sorbitol dehydrogenase stereo-selectively catalyses the reversible NAD-linked oxidation of various polyols and other secondary alcohols into their corresponding ketones. The kinetic constants are given for various novel polyol substrates, including -glucitol, -mannitol, -altritol, -altritol, -iditol and eight heptitols, as well as for many aliphatic and aromatic alcohols. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
(104 reference statements)
0
22
0
Order By: Relevance
“…The enzyme assays also showed that the predominant activity in extracts of sporangia exhibited the same biochemical features described for other members of the sorbitol dehydrogenase family (29). This included optimal activity at alkaline pH (pH 9 to 10), a preference for NAD as opposed to NADP as a cofactor, and broad substrate specificity.…”
Section: Vol 2 2003 Sporangium-specific Gene Expression In P Infesmentioning
confidence: 68%
See 2 more Smart Citations
“…The enzyme assays also showed that the predominant activity in extracts of sporangia exhibited the same biochemical features described for other members of the sorbitol dehydrogenase family (29). This included optimal activity at alkaline pH (pH 9 to 10), a preference for NAD as opposed to NADP as a cofactor, and broad substrate specificity.…”
Section: Vol 2 2003 Sporangium-specific Gene Expression In P Infesmentioning
confidence: 68%
“…These are typically broad-spectrum reversible oxidoreductases, in which conversions, such as mannitol to mannose or sorbitol to fructose, are coupled to NAD reduction (29). In true fungi, polyols, such as mannitol, arabitol, and glycerol, accumulate and exhibit multiple cellular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the pharmaceutical intermediate, enantio-pure (R)-or (S)-mandelic acid, is used in the synthesis of b-lactam antibiotics and analytical reagents (Groger, 2001), and (R)-mandelic acid may be made from (R)-1-phenyl-1,2-ethanediol (Drummond et al, 1990;Lindstad et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Sorbitol dehydrogenase (SDH) is another possible pathway for mannitol breakdown [43], as mannitol is an isomer of sorbitol [44] and SDH is found in Drosophila (Gene ID: 40836, 41313) [45]. Overloading of this pathway has been shown to lead to sorbitol accumulation in the gut [46] and the rate of mannitol catalysis by SDH is very low [43,47]. Taken together, D. melanogaster and its common microbes may be able to metabolize small amounts of mannitol, but likely not the amounts consumed in our experiment [48-51].…”
Section: Discussionmentioning
confidence: 99%